1995
DOI: 10.1111/j.1151-2916.1995.tb08480.x
|View full text |Cite
|
Sign up to set email alerts
|

Cristobalite Phase Formation in Glass/Ceramic Composites

Abstract: The effect of several different aluminum‐containing ceramic additions to borosilicate glass on suppressing cris‐tobalite precipitation has been examined. The results showed that mullite or aluminum nitride suppresses cristo‐balite formation more effectively than alumina or spinel. Although both follow a simple rule of mixtures, glass/mullite composites can be fabricated with lower dielectric constants than glass/alumina composites, while maintaining a thermal expansion coefficient close to Si. Electron micro‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…Past studies on borosilicate glasses which undergoes devitrification have shown that addition of alumina, aluminum nitride, cordierite and mullite can suppress the formation of cristobalite. 18,19 This finding coincides with our results supporting a strong influence of Al-cations on the crystallization of silica. Moreover, the literature data indicate that mullite most effectively suppresses the formation of cristobalite.…”
Section: Crystallization and Thermal Behavior Of Si(al)oc Bulk Ceramicssupporting
confidence: 94%
“…Past studies on borosilicate glasses which undergoes devitrification have shown that addition of alumina, aluminum nitride, cordierite and mullite can suppress the formation of cristobalite. 18,19 This finding coincides with our results supporting a strong influence of Al-cations on the crystallization of silica. Moreover, the literature data indicate that mullite most effectively suppresses the formation of cristobalite.…”
Section: Crystallization and Thermal Behavior Of Si(al)oc Bulk Ceramicssupporting
confidence: 94%
“…34 Cristobalite precipitation in the composite takes place during firing, but it can be prevented by the presence of Al ions. 35 The size and number of the fluorapatite crystals were influenced by ripening and dissolving effects, and the X-ray intensity of the apatite phase depended on the heat treatment temperature. 36 In addition, SEM observation showed that there were fewer pores in some materials as the number of firings increased.…”
Section: Discussionmentioning
confidence: 99%
“…7). Cristobalite is a polymorph of SiO 2 formed at 1048-1373 K in float glass and borosilicate glass [39,40]. Since the foam glasses are prepared at 1063 and 1083 K, the Si rich particles are likely cristobalite.…”
Section: Formation Of Percolated Foamsmentioning
confidence: 99%
“…To avoid sticking of the glass melt to the mould, the steel was coated with a kaolin suspension. The samples were then heated in air at 10 K/min to 1063 or 1083 K for different durations (5,10,20,40,80 and 160 min). The foams were cooled to 803 K (T g ) at 5 K/min and then to room temperature at~1 K/min.…”
Section: Preparation Of Foam Glassmentioning
confidence: 99%